Proceedings of Correlations and Fluctuations in Relativistic Nuclear Collisions — PoS(CFRNC2006) 2007
DOI: 10.22323/1.030.0022
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic flow from fast particles

Abstract: We study the interaction of a fast moving particle in the Quark Gluon Plasma with linearized hydrodynamics. We derive the linearized hydrodynamic equations on top of an expanding fireball, and detail the solutions for a static medium. There are two modes far from the jet -a sound mode and a diffusion mode. The diffusion mode is localized in a narrow wake behind the jet while the sound mode propagates at the Mach angle, cos(θ M ) = c s /c. A general argument shows that the strength of the diffusion mode relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…The possible hydrodynamic collective response of the plasma to the passage of an energetic parton through it was characterized earlier in refs. [171][172][173][174]; the holographic computation in refs. [123,125] provided a concrete realization in a full quantum field theoretical calculation, confirming that the anticipated hydrodynamic response could indeed be excited via the passage through the fluid of an energetic probe whose size is much smaller than 1/T .…”
Section: Medium Backreaction: Observable Consequences Of a Wake In Thmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible hydrodynamic collective response of the plasma to the passage of an energetic parton through it was characterized earlier in refs. [171][172][173][174]; the holographic computation in refs. [123,125] provided a concrete realization in a full quantum field theoretical calculation, confirming that the anticipated hydrodynamic response could indeed be excited via the passage through the fluid of an energetic probe whose size is much smaller than 1/T .…”
Section: Medium Backreaction: Observable Consequences Of a Wake In Thmentioning
confidence: 99%
“…[171][172][173][174] we shall treat the additional momentum acquired by the medium as a consequence of the passage of the jet as a small perturbation. (For studies of the nonlinear response of the plasma, see refs.…”
Section: Jhep03(2017)135mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, in position space, J n hydro probably has width comparable to Γ s (the attenuation length) and must be parametrized in some fashion. The authors of [1,36] used an equivalent of…”
Section: Relation To Linearized Hydrodynamicsmentioning
confidence: 99%
“…Further work [36] showed that for scenario 2 to match to data, the energy loss per distance needs to be chosen quite large-perhaps unrealistically so. Another study [51] included expansion of the plasma and used source terms similar to scenario 1.…”
Section: Jet-splitting and The Challenge Of Diffusion Wakesmentioning
confidence: 99%